Acoustical Parameters of Polystyrene in Binary Mixture - Venkateswara Rao, Amara; Raman, G.K.; Varada Rajulu, A. (Asian Journal of Chemistry, 2010)
Ultrasonic velocity, viscosity, density and refractive index measurements have been made for solutions of polystyrene (weight average molecular weight ≃ 2,46,600) in the binary mixture (benzene + carbon tetrachloride) at various concentrations ana temperatures. The molar compressibility (β), specific acoustic impedance(z), Rao number (R), van der waals constant (b) and the relaxation strength (r) have been computed. The variation of β, Z, R, b and r at 30 and 35ºC have been studied from which the presence of solute-solvent interaction has been revealed.